A textual analysis of theme and rheme structures in Malaysian editorials / Huzaifah A. Hamid - A. Hamid, Huzaifah (Universiti Teknologi MARA, 2018)
The present study aims to analyze the way writers use language in order to fulfill a purpose by measuring the similarities and differences in editorials with regard to Theme and Rheme choices. Two letters of opinion of an editorial were used in this study to investigate the thematic choices that might differ, given their different purposes. The results indicated that the writers presented the information directly without emphasizing on any proposition encoded in the clauses. Besides, it was also found that the intervention made by the writers is less obvious, as measured by the low occurrences of Interpersonal Theme. In addition, it can also be concluded that the letter of support is more cohesive than the letter of oppose because of its higher occurrences of Textual Theme.